KONSEP SUPERVISI PENDIDIKAN - Meti Fatimah; Asmira Efend; Muhamad Abdul Azis (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2025)
Educational supervision is an essential strategy for improving the quality of learning and teacher professionalism. The development of the supervision paradigm indicates a shift from an authoritative control approach to a collaborative, reflective, and humanistic professional development process. This article aims to examine the concept of educational supervision, including its definition, objectives, functions, principles, scope, and implementation challenges in schools. This article is based on a literature review by analyzing various expert opinions and relevant research findings. The results show that educational supervision plays a role as a continuous professional development process that supports the improvement of teachers’ pedagogical and professional competencies as well as the quality of learning. However, its implementation still faces several challenges, such as limited supervisor competence, negative teacher perceptions, high administrative burdens, limited time, and weak follow-up actions. Therefore, systematic efforts are needed to enhance the effectiveness of educational supervision in order to contribute significantly to improving educational quality.